The dependence of the financial stability of construction enterprises on the phase of the economic cycle - Sysko, O. G.; Saacian, А. (Ліра-К, 2022)
The financial stability of construction enterprises depends on many factors (terms of mutual settlements for construction products, efficiency of operational, financial, investment activities, presence or absence of own capital, liquidity of property, sufficiency of own working capital, etc.), including the phase of the economic cycle [1] and can be one of the criteria for the investment attractiveness of enterprises of various industries, types of activities and sectors of the economy.
Keywords: economic cycle; financial stability; constructioh enterprises